PEMBUATAN JALUR EVAKUASI ALTERNATIF BERDASARKAN MODEL SIMULASI BANJIR LUAPAN SUNGAI BENGAWAN SOLO DI KOTA SURAKARTA MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS (SIG) - Yuli Priyana; Priyono -; Alif Noor Anna; Agus Anggoro Sigit; Rudiyanto - (Universitas Muhammadiyah Semarang, 2015)
The aim of this research is to create a disaster evacuation paths based on the results of flood modeling. The method used in this research is least cost path. The results obtained from this study were (a) the impact of a simulation model to land use is the buildings area 885,36 m2, water area 10.621,97 m2, vacant land with rare vegetation area 68.916,64 m2, vacant land with vegetation area 78.925,16 m2, and settlement area 137.251,78 m2, and (b) evacuation paths produced by the method of least cost path is two lanes in Kampung Sewu and 2 lanes in the village of Jebres. The least cost path choose lane from the first starting point in intersection of three road of Beton and go accros Gotong Royong road to evacuation point in Jami’Mosque. Both of the starting point in the Bengawan Solo river embankment can to the evacuation point Sawunggaling Mosque. Jebres evacuation route in the village there are two lines of evacuation. The first lane evacuation from the starting point in intersection three road of Kentingan to the front Psychiatric Hospital Surakarta, and then to the front office Psychotherapy Center Surakarta North toward straight up in Al-Fath Mosque. Both are alternative evacuation route from the starting point in a four-way intersection in the middle of densely populated settlements can pass the road to the west to get stuck, then straight over the bridge, past the front of the Student Dormitory UNS, then to the evacuation site Al-Fath Mosque.Keywords: simulation model, evacuation route, GIS